2021
DOI: 10.1111/labr.12206
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of female labour force participation: Evidence from Greece

Abstract: The present study investigates long-term trends in female participation in the Greek labour market. The analysis presented decomposes the growth in the female participation rate between 1992 and 2020. The dataset used is the Greek Labour Force Survey (GLFS). The model type used is a binary age-period-cohort Probit model and a multinomial choice Probit model. A number of assumptions are made to identify the three effects separately. Model I use lagged unemployment as a proxy variable for the period effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…According to Kang (2021), countries with more work-oriented study programs have lower youth unemployment than other countries. Dvouletý et al (2020) and Marelli and Vakulenko (2016) showed a higher unemployment rate for younger individuals, Dvouletý et al (2020), Lallukka et al (2019), Lim and Lee (2019), Petrakis (2021) and Schioppa and Lupi (2002) for females and Dvouletý et al (2020) for people from ethnic minority groups. Similar results were also achieved by Dagume and Gyekye (2016), Maynou et al (2022) and Wesseling (2021).…”
Section: Literature Reviewmentioning
confidence: 93%
“…According to Kang (2021), countries with more work-oriented study programs have lower youth unemployment than other countries. Dvouletý et al (2020) and Marelli and Vakulenko (2016) showed a higher unemployment rate for younger individuals, Dvouletý et al (2020), Lallukka et al (2019), Lim and Lee (2019), Petrakis (2021) and Schioppa and Lupi (2002) for females and Dvouletý et al (2020) for people from ethnic minority groups. Similar results were also achieved by Dagume and Gyekye (2016), Maynou et al (2022) and Wesseling (2021).…”
Section: Literature Reviewmentioning
confidence: 93%
“…The two-thirds gender rule increased the demand for women in the labour force, thus reducing the youth unemployment rate. The increase in per capita income in Kenya supported the argument by Khraise (2019) that linked the employment of women with favourable economic conditions. The findings were also agreed with those of Anyanwu (2016), who showed a positive relationship between GDP per capita and gender equality.…”
Section: Pre-estimation Proceduresmentioning
confidence: 72%